The achievement of the super short channel control in the magnetic Ge n-FinFETs with the negative capacitance effect. (June 2017) - Liao, Ming-Han; Huang, Hong-Yi; Tsai, Fu-An; Chuang, Chih-Chieh; Hsu, Min-Hsuan; Lee, Chang-Chun; Lee, Min-Hung; Lien, Chin; Hsieh, Cho-Fan; Wu, Teng-Chun; Wu, Hung-Sen; Yao, Chun-Wei
Abstract: Super short channel control (sub-threshold swing = 95 mV/dec) in Ge n-type Fin Field-Effect Transistors (n-FinFETs) is achieved through the promising gate stack characteristics of gate leakage (Jg )-equivalent-oxide-thickness (EOT) and ultra-high k-value (∼312) with the implement of the magnetic gate stack scheme. On the other hand, the negative capacitance effect is also observed in the magnetic Ge n-FinFETs by the extraction of the body factor (m = 0.47) at low temperature measurement. The proposed magnetic gate stack scheme (tetragonal-phase BaTiO3 as the dielectric layer and magnetic FePt film as the metal gate) in the Ge n-FinFETs has super Jg -EOT characteristics, negative capacitance phenomenon, and promising transistor performance. It provides the useful solution for the future low power mobile devices designed on the high mobility (Ge) material.